From Co-Ops to Community Land Trusts: Tracing the Historical Evolution and Policy Mobilities of Collaborative Housing Movements. Issue 1 (1st January 2020) - Thompson, Matthew
ABSTRACT: This article explores the historical development of two different collaborative housing models: Liverpool's housing co-operative movement of the 1970s, when public tenants successfully struggled for collective dweller control in designing, developing and managing their own housing; and, today, Liverpool's nascent urban community land trust (CLT) movement. The genesis and institutionalization of each is analysed through mobile urbanism, policy mobilities and planning histories perspectives. Both Liverpool's co-ops and CLTs are shown to have been mobilized through ideas adapted from elsewhere, mutating upon exposure to contextual factors embedded in place. Contemporary CLT campaigns can be traced back to various sources: CLT experiments by professional or arms-length state agencies; and previous periods of collaborative housing activism, notably the 1970s co-ops. The article situates these movements within a collaborative housing conceptual framework and draws out the implications of these genealogical findings for the further development of collaborative housing.